The prognostic value of T-peak T-end among patients with implantable cardiac defibrillator for secondary prevention (Annals of Medical Research, 2021)
Aim: Cardiac death due to ventricular arrhyhtmias can occur in patients with ICD (implantable cardioverter defibrillator) for secondaryprevention. The aim of this study is to assess the prognostic value of electrocardiographic ventricular repolarization parameters inpatients with secondary prevention.Materials and Methods: Sixty five patients with ICD for secondary prevention after sustained ventricular tachycardia, ventricularfibrillation or sudden cardiac death were enrolled to the study retrospectively. Patients were divided into groups according tomortality during a follow up period of 4,5 years (48 patients alive and 17 dead). Heart rate, QT, QTc and T peak T end (Tp-e) durationwere measured from 12 derivations ECG electronically.Results: Mean age of the study population was 70.6±11.9 years. Ventricular repolarization parameters such as QT, QTc, Tp-e durationand Tp-e index values were found to be similar between deaths and live patient groups. Patients who died during the follow-up hadadvanced age (68.7±12.5 vs 76.8±10.3 years, p=0.009), lower left ventricular ejection fraction percentage (LVEF %) (37.6±13.3 vs26.9±9.2, p=0.003) and lower estimated glomerular filtration rate (81.2±22.5 vs 61±34.3 ml/min/m2, p=0.03). Arrhythmic deathpatients only had lower LVEF % than non-arrhythmic death patient’s group.Conclusions: In patients with ICD for secondary prevention QT, QTc, Tp-e duration and Tp-e index were not related to mortality.